2013
DOI: 10.1107/s0907444913002771
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cryoprotectants on the structure and thermostability of the human carbonic anhydrase II–acetazolamide complex

Abstract: Protein X-ray crystallography has seen a progressive shift from data collection at cool/room temperature (277-298 K) to data collection at cryotemperature (100 K) because of its ease of crystal preparation and the lessening of the detrimental effects of radiation-induced crystal damage, with 20-25%(v/v) glycerol (GOL) being the preferred choice of cryoprotectant. Here, a case study of the effects of cryoprotectants on the kinetics of carbonic anhydrase II (CA II) and its inhibition by the clinically used inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…1B; Table 4). The promotion of more favorable C-H···π interactions among the F226 aromatic cluster upon CO 2 binding may contribute significantly to thermostability as has been seen in previous ligand-HCA II complexes (1, 34) and among other proteins (41-43). The extra stability inferred from reorientation of F226 upon ligation of CO 2 may provide additional protection against oxidative (44, 45) and acidic (46, 47) microenvironments encountered within the cell.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…1B; Table 4). The promotion of more favorable C-H···π interactions among the F226 aromatic cluster upon CO 2 binding may contribute significantly to thermostability as has been seen in previous ligand-HCA II complexes (1, 34) and among other proteins (41-43). The extra stability inferred from reorientation of F226 upon ligation of CO 2 may provide additional protection against oxidative (44, 45) and acidic (46, 47) microenvironments encountered within the cell.…”
Section: Discussionmentioning
confidence: 75%
“…The proton-shuttle residue H64 (11) was seen to be in a dual conformation, ‘in’ and ‘out’, for the F226L and F226W variants, but was found only in the ‘in’ conformation (i.e., towards the active site) in the F226I variant. These variable conformations among crystallographic structures of HCA II are not an uncommon occurrence and are dependent on the crystallization conditions (1, 9, 10, 33, 34). …”
Section: Resultsmentioning
confidence: 99%
“…Although the binding sites relevant for drug design (sites 1-4) reported here are very similar among the human catalytic CAs, the fragment-addition approach could be combined with a tail approach to design more isoform-specific inhibitors, as discussed previously (Aggarwal, Kondeti et al, 2013b). This approach offers a great opportunity, as is shown by carbohydrate (glycerol; Aggarwal, Boone et al, 2013) binding near the active site of CA isoforms.…”
Section: Resultsmentioning
confidence: 88%
“…High-resolution X-ray [ 75 , 76 ] and neutron structures [ 29 ] of HCA II in complex with acetazolamide (Diamox), a tight binding inhibitor used in the treatment of glaucoma [ 12 , 77 ], has accelerated research into structural-based rational design of an isozyme specific inhibitor. Current research interest includes specific inhibition of HCA IX, which has been shown to be overexpressed in a wide array of cancer cell lines [ 11 , 39 , 78 , 79 , 80 ].…”
Section: Pharmalogical Considerationsmentioning
confidence: 99%